AB0546 Clinical and functional remission based on newly defined ACR/EULAR remission criteria achieved with tocilizumab in patients with rheumatoid arthritis. (23rd January 2014) - Hanami, K.; Saito, K.; Tasaka, H.; Tanaka, Y.
Abstract : Background: Although the efficacy of tocilizumab for rheumatoid arthritis (RA) has been reported in many clinical trials, there have been few reports of the efficacy evaluated based on CDAI, SDAI and newly defined ACR/EULAR remission criteria under daily clinical practice. Objectives: To explore how to make the best use of tocilizumab in terms of the achievement of the new remission criteria by demonstrating its efficacy through clinical and structural evaluations in patients with RA during clinical practice. Methods: This study evaluated 87 patients with RA who had received 8 mg/kg of tocilizumabat 4-week intervals in our institution and had been followed up for at least 104 weeks after initial treatment. Clinical information was extracted from their medical records. Clinical efficacy was evaluated based on CDAI, SDAI and HAQ. Clinical remission was defined as the achievement of DAS-28 <2.6, CDAI ≤2.8 and SDAI ≤3.3 as well as the criteria based on Boolean approach: swollen joints ≤1, tender joints ≤1, C-reactive protein (CRP) ≤1 mg/dL and patient global assessment ≤1 cm. Missing data in withdrawals were imputed using last observations carried forward (LOCF). Results: Eighty seven patients with RA evaluable for efficacy had a mean age of 58.5 years, disease duration of 11.9 years. Of them, 48.4% used methotrexate concomitantly and 56.3% had used other biological products before tocilizumab therapy. At baseline, almost all patients had high disease activity, mean DAS28 was 5.9±1.3, mean SDAI was 30.1±14.9 and mean CDAI was 27.5±14.3. The clinical remission rates based on individual criteria were 48.3% for DAS28, 18.4% for CDAI and 21.8% for SDAI. The remission rate based on the new ACR/EULAR remission criteria (Boolean definition) was 18.4%. Activities of daily living were evaluated using HAQ, which was decreased from 1.7 at baseline to 1.2 at Week 104. Functional remission (HAQ ≤0.5) was achieved by 30.9% of the patients. Logistic analysis was performed to compare Boolean-related factors at Week 104 between patients with remission (n=16) and those without remission (n=71). The analysis revealed that shorter disease duration (<2 years) was associated with remission at Week 104 (Odds ratio 9.547, p=0.007). Patients with a disease duration of <2 years could achieve a remission rate of 53.3% even when the Boolean criteria were applied (as shown in the table). Conclusions: As this study demonstrated the efficacy of tocilizumab for RA based on the new remission criteria in clinical practice, it is suggested that use of tocilizumab in patients with shorter disease duration will allow the achievement of higher clinical and functional remission rates. Disclosure of Interest: K. Hanami: None Declared, K. Saito: None Declared, H. Tasaka Employee of: Chugai Pharma, Y. Tanaka Consultant for: Mitsubishi-Tanabe Pharma, Pfizer Inc., Speakers Bureau: Mitsubishi-Tanabe Pharma, Takeda Pharmaceutical Co Ltd, Abbott, Eisai Pharma, Chugai Pharma